1983
DOI: 10.1159/000182962
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Patterns in Hemodialysis Patients with and without HBV Infection

Abstract: 66 patients from 5 dialysis centers were surveyed for the prevalence of HBV markers. Their immune status was evaluated by studying parameters of cellular and humoral immunity. Results showed that all patients had depressed T cell numbers while B cell counts, IgG, IgA, IgM, IgD and C3 levels were normal. However, the group of patients who had persistent HBs antigenemia also had persistence of HBeAg, negative responsiveness to skin testing and high IgE levels. The group with HBsAb had negative reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Nevertheless, both assays are not entirely comparable because they are different in methodology, and, moreover, in their report DApiceet al [3], do not differentiate between radiosensi tive and radioresistant suppressor functions. The prob able monocyte defect suggested in our report is in agree ment with previous reports showing other alterations in monocyte function in HD patients, such as an enhanced attachment, spreading activity and impaired phagocyto sis of IgG-coated human erythrocytes [4]. It is wellknown that macrophages after being activated can in crease their spreading on glass and increase their content of lysosomal enzymes, but at the same time some other functions are decreased such as their antigen presenting properties [30].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Nevertheless, both assays are not entirely comparable because they are different in methodology, and, moreover, in their report DApiceet al [3], do not differentiate between radiosensi tive and radioresistant suppressor functions. The prob able monocyte defect suggested in our report is in agree ment with previous reports showing other alterations in monocyte function in HD patients, such as an enhanced attachment, spreading activity and impaired phagocyto sis of IgG-coated human erythrocytes [4]. It is wellknown that macrophages after being activated can in crease their spreading on glass and increase their content of lysosomal enzymes, but at the same time some other functions are decreased such as their antigen presenting properties [30].…”
Section: Discussionsupporting
confidence: 92%
“…The 'in vitro' analysis of the lymphocyte function demonstrates an alteration of cell-mediated immunity due to a diminished response to mitogenic challenge, and other abnormal cell-mediated reactions [1,2,4,[6][7][8]10]. This cell-mediated immunodeficiency has been attri buted to an increased suppressor function [6,[13][14][15] or to the expression of a 'pan-deficiency' in the PBL function [3,9], Investigators who postulate the active suppressor theory suggest that the monocyte could be responsible [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, this depressed LPR probably contributed to the inability of patients on HD to clear HBV. In this regard, Samra et al [12] also found immunological differences between groups of HD patients who had persistent HBV antigenemia as compared with those who were HBs antibody positive. Although both groups showed negative delayed skin hypersensitivity responses, the group with HBs antigenemia also had an increase in serum IgE levels, sug gesting a loss in suppressor T cell activity.…”
Section: Discussionmentioning
confidence: 94%